State-wide comparative analysis of the cost saving potential of Vuilleumier heat pumps in residential houses. (1st November 2020) - Shi, Peng; Wang, Lin-Shu; Schwartz, Paul; Hofbauer, Peter
Highlights: A heat driven heat pump uncaps the natural gas end-use efficiency of 100% Annual cost savings analysis shows great potentials for Vuilleumier heat pumps. Annual energy cost for heating, cooling and water heating across the United States. Seasonal electricity and natural gas demand shifts with Vuilleumier heat pumps. The use of Vuilleumier heat pumps smooth the seasonal gas demand fluctuations. Abstract: The Vuilleumier cycle-based heat pump is a promising technology that can break the capped natural gas end-use efficiency of 100%. This study compares the natural gas driven Vuilleumier cycle-based heat pumps with the common electricity driven vapor compression cycle-based heat pumps in terms of the exergy efficiency and the operating cost. Cycle analysis is performed to show the relations between the existing devices, their ideal counterparts, and the absolute thermodynamic limit of an ideal Carnot heat pump. With regards to operating cost, these two types of heat pumps are benchmarked in building energy simulations against the commonly used system of space heating, cooling and water heating equipment, to show the annual operating cost saving or deficit across the United States. In addition, three locations are selected to show the detailed annual operating cost and the energy demand profile. The results suggest that the Vuilleumier cycle-based heat pumps can be highly cost effective across the United States with an annual operating cost savings as high as $1230 in Vermont or an annual percentage cost savings as high as 52% in California.